2019
DOI: 10.1101/817320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monitoring of Plasmodium falciparum and Plasmodium vivax using microsatellite markers indicates limited changes in population structure after substantial transmission decline in Papua New Guinea

Abstract: Monitoring the genetic structure of malaria parasite populations has been proposed as a novel and sensitive approach to quantify the impact of malaria control and elimination efforts. Here we describe the first population genetic analysis of sympatric Plasmodium falciparum (Pf) andPlasmodium vivax (Pv) populations following nationwide distribution of long-lasting insecticide treated nets (LLIN) in Papua New Guinea (PNG). Parasite isolates from serial cross-sectional studies pre-(2005-6) and post-LLIN (2010-201… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 107 publications
(176 reference statements)
0
9
0
Order By: Relevance
“…Genomic studies of local transmission and importation in low and medium endemicity countries are becoming more common in the literature and starting to shed light on the dynamics of parasite movement (Chenet et al, 2012;Daniels et al, 2015;Gwarinda et al, 2021;Kattenberg et al, 2020; Morgan AP, Brazeau NF, Ngasala B, Mhamilawa LE, Denton M, Msellem M, Morris U, Filer DL, Aydemir O, Bailey JA, Parr JB, Mårtensson A, Bjorkman A, Juliano JJ, n.d.; Noviyanti et al, 2015;Roh et al, 2019;Tessema et al, 2019). However, relatively few studies have used genomic approaches to study malaria transmission dynamics and importation on small geographic scales, such as a single district (Searle et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic studies of local transmission and importation in low and medium endemicity countries are becoming more common in the literature and starting to shed light on the dynamics of parasite movement (Chenet et al, 2012;Daniels et al, 2015;Gwarinda et al, 2021;Kattenberg et al, 2020; Morgan AP, Brazeau NF, Ngasala B, Mhamilawa LE, Denton M, Msellem M, Morris U, Filer DL, Aydemir O, Bailey JA, Parr JB, Mårtensson A, Bjorkman A, Juliano JJ, n.d.; Noviyanti et al, 2015;Roh et al, 2019;Tessema et al, 2019). However, relatively few studies have used genomic approaches to study malaria transmission dynamics and importation on small geographic scales, such as a single district (Searle et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These low transmission settings offer a unique opportunity to observe long-term dynamics of parasites across seasons, as the smaller number of parasites may be easier to track from a lack of recombination with genetically distinct parasites within the mosquito. A small number of studies have attempted to observe temporal population changes in these regions, and even fewer have been able to combine temporal and geospatial data to identify hotspots over space and time (Chenet et al, 2012;Daniels et al, 2015;Gwarinda et al, 2021;Kattenberg et al, 2020;Noviyanti et al, 2015;Roh et al, 2019;Tessema et al, 2019). Most of these studies evaluated parasite population changes over relatively large geographic distances.…”
Section: Introductionmentioning
confidence: 99%
“…Multilocus microsatellite genotyping is a validated tool for examining P. falciparum diversity and population structure and has been successfully used to characterise parasite populations across endemic regions in sub‐Saharan Africa, South America, Southeast Asia, and the Pacific (Anderson et al, 2000; Anthony et al, 2005; Barry et al, 2013; Kattenberg et al, 2020; Machado et al, 2004; Mobegi et al, 2012; Vera‐Arias et al, 2019; Yalcindag et al, 2012). These studies have shown that in high‐transmission settings (e.g., sub‐Saharan Africa) where the majority of infections are multiclonal, the P. falciparum population is characterised by high diversity, low levels of population differentiation, and linkage equilibrium, increasing the likelihood of recombination between genetically distinct parasite clones (i.e., outcrossing) in the mosquito following a blood meal.…”
Section: Introductionmentioning
confidence: 99%
“…Multilocus microsatellite genotyping is a validated tool for examining P. falciparum diversity and population structure and has been successfully used to characterise parasite populations across endemic regions in sub-Saharan Africa, South America, Southeast Asia, and the Pacific (Anderson et al, 2000;Anthony et al, 2005;Barry et al, 2013;Kattenberg et al, 2020;Machado et al, 2004;Mobegi et al, 2012;Vera-Arias et al, 2019;Yalcindag et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, population surveillance widely utilized genotyping tools targeting surface antigens by PCR to distinguish parasite clones (22,23), followed by panels of microsatellites that are not under evolutionary selection pressure and, therefore, more suitable to inform population genetic changes (24)(25)(26). Despite its popularity, MS-typing is difficult to standardize, complicating comparisons between research studies (27) and is not very suitable to genotype using short-read sequencing technologies due to the repetitive nature of the alleles. More recently, genome-wide single nucleotide polymorphism (SNP) panels capable of defining a "molecular barcode" to capture the diversity of parasite populations have been developed and can be investigated with methods such as microarrays, real-time PCR, and deep sequencing (28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%